Morphology Evolution in High‐Performance Polymer Solar Cells Processed from Nonhalogenated Solvent. Issue 8 (26th May 2015) - Cai, Wanzhu; Liu, Peng; Jin, Yaocheng; Xue, Qifan; Liu, Feng; Russell, Thomas P.; Huang, Fei; Yip, Hin‐Lap; Cao, Yong
<x xml:space="preserve">Abstract</x> A new processing protocol based on non‐halogenated solvent and additive is developed to produce polymer solar cells with power conversion efficiencies better than those processed from commonly used halogenated solvent‐additive pair. Morphology studies show that good performance correlates with a finely distributed nanomorphology with a well‐defined polymer fibril network structure, which leads to balanced charge transport in device operation.